2020
DOI: 10.21512/bbr.v11i3.6464
|View full text |Cite
|
Sign up to set email alerts
|

Consumer’s Impulse Buying Behavior: Do Visual Merchandising, Store Atmosphere, Availability of Money, and Promotional Activity Affect it?

Abstract: The research aimed to analyze the influence of visual merchandising, store atmosphere, availability of money, and promotional activity on impulse buying behavior in MINISO Pekanbaru. The research applied a quantitative method, and the population was consumers who purchased any product in MINISO Pekanbaru. The sample amounted to 150 respondents with an accidental sampling technique. The instrument used was a questionnaire by asking questions to respondents. Analysis was conducted by using a multiple regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Sales promotion also attracts attention and create a desire to buy, and the effectiveness depends on the consumer and situational context. Certain consumers may be more influenced by discounts or promotional offers, while others may not be impressed by the incentives (Wijaya and Setyawan, 2020).…”
Section: Figure 1 Hypothesis Testing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sales promotion also attracts attention and create a desire to buy, and the effectiveness depends on the consumer and situational context. Certain consumers may be more influenced by discounts or promotional offers, while others may not be impressed by the incentives (Wijaya and Setyawan, 2020).…”
Section: Figure 1 Hypothesis Testing Resultsmentioning
confidence: 99%
“…Therefore, the following hypothesis is proposed: H1: Celebrity endorser has a positive influence on impulsive buying Promotion is one aspect of consumer stimulation in making impulsive buying. This is because sales promotion is considered a marketing activity with added value to increase the sales volume of a product (Wijaya and Setyawan, 2020). The act of shopping often evolves into a habitual practice, where consumers allocate a portion or the entirety of the financial resources in pursuit of the desired products (Simbolon, Nurcholifa and Safarina, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Money can induce a good mood and diminish a bad mood in shopping circumstances, influencing the desire to buy (Beatty & Ferrell, 1998). Wijaya and Setyawan (2020) also found that money availability has a significant relationship with the desire to buy impulsively. This indicates that as money becomes more available, the desire to buy impulsively increases, potentially affecting impulsive purchasing behavior in line with (Badgaiyan et al, 2016, Foroughi et al, 2012.…”
Section: Money Availabilitymentioning
confidence: 89%
“…Consideration on impulsive buying behaviour becomes increasing attention due to consumers' behaviour changed with the Covid 19 pandemic in globally [28]. Wijaya and Setyawan [4] defined impulsive buying behaviour as an unplanned, spontaneous, and sudden purchase decision of the customer. Further, Babu and Mathew [2] opined that the impulsive buying behaviour is a very powerful process that takes place in the mind, disrupting the normal decision making patterns of the consumer's brain.…”
Section: Impulsive Buying Behaviourmentioning
confidence: 99%
“…Consumer buying behaviour is the process by which consumers select, purchase, and consume goods to satisfy their needs based on various factors [3]. In studying the behaviour, impulsive buying behavior receives impressive attention specifically for apparel products [4]. In such manner, consumers motivated from various stimulants to buy products without a second thought and this is identified as a mental process and an uncontrollable process.…”
Section: Introductionmentioning
confidence: 99%